LIBERDADE DE EXPRESSÃO, DISCURSO ANTIDEMOCRÁTICO E IMUNIDADE PARLAMENTAR: BREVE ANÁLISE DA PRISÃO DO DEPUTADO FEDERAL DANIEL SILVEIRA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present work intends to reflect and discuss the scope of application of the constitutional guarantee of freedom of expression, taking as a concrete case the analysis of the constitutional aspects involving the arrest of Federal Deputy Daniel Silveira, due to a speech promoted on social networks, interpreted by the Supreme Court Federal as undemocratic. Through the bibliographical review with the application of the inductive method, this research discusses the guarantee of freedom of expression with a brief analysis of relevant judgments of the Federal Supreme Court on the subject, notably ADPF 572 which declared the constitutionality of Ordinance 69/ 2019 and which led to the establishment of the "Fake News Inquiry". Also, brief considerations will be explained regarding parliamentary immunity and how the institutes of freedom of expression and parliamentary immunity were considered in the specific case, resulting in the Federal Deputy's arrest in flagrante delicto.